Move the 'j' terms to one side and the constants to the other. This will result in
3j = -18
Divide both sides by 3 for the final answer.
4j+8=j-10
I don't know how to figure out the j value.
2 answers
Simplifying
4j + 8 = j + -10
Reorder the terms:
8 + 4j = j + -10
Reorder the terms:
8 + 4j = -10 + j
Solving
8 + 4j = -10 + j
Solving for variable 'j'.
Move all terms containing j to the left, all other terms to the right.
Add '-1j' to each side of the equation.
8 + 4j + -1j = -10 + j + -1j
Combine like terms: 4j + -1j = 3j
8 + 3j = -10 + j + -1j
Combine like terms: j + -1j = 0
8 + 3j = -10 + 0
8 + 3j = -10
Add '-8' to each side of the equation.
8 + -8 + 3j = -10 + -8
Combine like terms: 8 + -8 = 0
0 + 3j = -10 + -8
3j = -10 + -8
Combine like terms: -10 + -8 = -18
3j = -18
Divide each side by '3'.
j = -6
Simplifying
j = -6
4j + 8 = j + -10
Reorder the terms:
8 + 4j = j + -10
Reorder the terms:
8 + 4j = -10 + j
Solving
8 + 4j = -10 + j
Solving for variable 'j'.
Move all terms containing j to the left, all other terms to the right.
Add '-1j' to each side of the equation.
8 + 4j + -1j = -10 + j + -1j
Combine like terms: 4j + -1j = 3j
8 + 3j = -10 + j + -1j
Combine like terms: j + -1j = 0
8 + 3j = -10 + 0
8 + 3j = -10
Add '-8' to each side of the equation.
8 + -8 + 3j = -10 + -8
Combine like terms: 8 + -8 = 0
0 + 3j = -10 + -8
3j = -10 + -8
Combine like terms: -10 + -8 = -18
3j = -18
Divide each side by '3'.
j = -6
Simplifying
j = -6